Correlation Between Egg Production Performance of Sikumbang Jonti Ducks as a Selection Method in Smallholder Farms - Rafian, Teguh; Yurnalis, Yurnalis; Husmaini, Husmaini; Arlina, Firda; Wanniatie, Veronica; Husni, A. (Jurnal Sain Peternakan Indonesia, 2025)
This study aims to determine the diversity and correlation of egg production performance in Sikumbang Jonti ducks as a basis for making selection decisions. The materials used were 47 female Sikumbang Jonti ducks. In the production phase, Sikumbang Jonti ducks were intensively reared in individual battery cages for 24 weeks. The observed variables were body weight (g), age at first laying (days), egg production (eggs), and egg weight (g). Data on body weight, age at first laying, total egg production, and egg weight were analyzed descriptively by calculating the mean value, standard deviation, coefficient of variation, minimum value, and maximum value. Furthermore, data on body weight, age at first laying, egg production, and egg weight were also analyzed for correlation to see the direction and relationship between variables. The results of this study were that Sikumbang Jonti ducks have an average body weight of 1299g, age at first egg laying of 170.19 days, average total egg production of 36.62 eggs, and average egg weight of 59.06g. The diversity of body weight, age at first egg laying, and egg weight of Sikumbang Jonti ducks are moderate, while the diversity of egg production is high. The diversity of body weight, age at first laying, and egg weight of Sikumbang Jonti ducks are included in moderate diversity. In contrast, the diversity of egg production is included in high diversity. Based on the correlation of body weight, age at first laying, egg production, and egg weight of Sikumbang Jonti ducks, age at first laying is the selection variable that can be used as a good predictor of egg production performance. In conclusion, the study results show that a longer age of first laying can be used as a selection variable to increase the production and egg weight of Sikumbang Jonti ducks.